Proactive CSR: analytical hierarchy process and empirical assessment in the French context - Ipag Business School; Achabou, Mohamed Akli; Dekhili, Sihem; Prince, Linda (Paris, 2014)
"The main objective of this research is to study the determinants of the environmental commitment in France. 25 companies responded to a survey. The results show that the regulation constitutes a relevant vector of the environmental commitment of companies but it comes in a second order after the customer satisfaction. The search for legitimacy with the customers seems to be fundamental for the enterprises’ survival."